Chapter 6 Part 1
Chapter 6 Part 1
Chapter 6 Part 1
Laplace Transforms
6.1 Introduction
T : F1 → F2 .
For the differerential operator D, we have F1 = {all differentiable functions}, whereas for the integral oper-
ator I we might have F1 = {all continuous functions}.
A useful tool for solving differerential equations is that of an integral transform, particularly on of the form:
Z β
T [f ](s) = K(x, s)f (x) dx.
α
The function K(x, s) is called the kernel, and the transform is usually denoted as F = T [f ]. Several
transforms have been found useful: Laplace, Fourier, Mellin, Hankel, . . . , others. We will only consider
Laplace transforms.
82
Math 334 6.1. INTRODUCTION 83
Remark. This is an improper integral, so it doesn’t converge for just any old function f . ◭
We will use Laplace transforms to solve ODEs in the following manner. First take the Laplace transform of
the ODE to get an algebraic equation in Y = L[y]. This algebraic equation is linear in Y , and so is eaasily
solved. Then take the inverse Laplace transform to get the solution to the original equation. The procedure
is represented by the schematic in Figure 6.1.
Laplace
linear ODE transform algebraic equation
F(x,y,y’,y’’)=0 G(s,Y)=0
solve
inverse Laplace
solution transform solution
y(x) Y(s)
Consider the behaviour of a function f near a point x0 , in particular consider the following limits:
f (x+
0 ) := lim+ f (x), f (x−
0 ) := lim− f (x).
x→x0 x→x0
Definition 6.2. If
(i) f (x+ −
0 ) = f (x0 ) = f (x0 ), then f is continuous at x0 ;
+
(ii) f (x0 ) = f (x− 0 ) 6= f (x0 ), then f has a removable discontinuity at x0 ;
(iii) f (x+ −
0 ) 6= f (x0 ), then f has a jump discontinuity at x0 ;
+
(iv) either f (x0 ) or f (x− 0 ) does not exist, then f has a “bad” discontinuity at x0 . ◭
Remark. A function f is piecewise continuous on an interval (a, b) if f has at most a finite number of
Math 334 6.1. INTRODUCTION 84
Example 6.6. The functions f (x) = 1/x and g(x) = sin(1/x) are not piecewise continuous on the interval
(0, 1), since
1 1
f (0+ ) = lim+ f (x) = lim+ and g(0+ ) = lim+ g(x) = lim+ sin do not exist.
x→0 x→0 x x→0 x→0 x
Definition 6.7. P C(a, b) := {set of all piecewise continuous functions on (a, b)} ◭
The set of piecewise continuous functions P C(a, b) satisfy the following properties:
(1) f, g ∈ P C(a, b) =⇒ αf + βg ∈ P C(a, b) ∀α, β ∈ R;
(2) f, g ∈ P C(a, b) =⇒ f g ∈ P C(a, b);
Rb
(3) f ∈ P C(a, b) =⇒ a
|f (x)| dx exists.
Definition 6.8. A function f is said to be of exponential order if there exist constants M, x̄ and a, with
M, x̄ > 0 such that |f (x)| 6 M eax for x > x̄. ◭
Example 6.9. The functions x, e2x , and cos 3x are of exponential order since
Theorem 6.10.
If (i) f ∈ P C(0, ∞); and (ii) f is of exponential order (i.e. |f (x)| 6 M eax for x > x̄),
then the Laplace transform L[f (x)] =: F (s) exists for s > a.
Proof
Z ∞ Z x̄ Z ∞
−sx −sx
e f (x) dx = e f (x) dx + e−sx f (x) dx =: I1 + I2 .
0 0 x̄
Math 334 6.2. PROPERTIES OF LAPLACE TRANSFORMS 85
Since f ∈ P C(0, x̄) and e−sx ∈ P C(0, x̄) for every s, it follows from properties 2 and 3 listed earlier that
e−sx f (x) ∈ P C(0, x̄) and hence I1 exists.
Theorem 6.12.
If (i) f ∈ P C(0, ∞); (ii) f is of exponential order; and (iii) F (s) = L[f (x)], then
lim F (s) = 0.
s→∞
Proof
Exercise.
Example 6.13.
1 1
For f (x) = 1 we have F (s) = and lim F (s) = lim = 0.
s s→∞ s→∞ s
1 1
For f (x) = eax we have F (s) = and lim F (s) = lim = 0.
s−a s→∞ s→∞ s − a
s s
For f (x) = cos ax we have F (s) = 2 2
and lim F (s) = lim 2 = 0.
a +s s→∞ s→∞ a + s2
Math 334 6.2. PROPERTIES OF LAPLACE TRANSFORMS 86
Theorem 6.14.
The Laplace transform is a linear operator on F1 , i.e.
L[af + bg] = aL[f ] + bL[g] ∀a, b ∈ R, ∀f, g ∈ F1 .
Proof
Z ∞ Z ∞ Z ∞
−sx −sx
L[af + bg] = e (af (x) + bg(x)) dx = a e f (x) dx + b e−sx g(x) dx = aL[f ] + bL[g].
0 0 0
Example 6.16. Find the Laplace transform of cosh ax and sinh ax.
Solution
eax + e−ax
1 ax −ax
1 1 1 s
L[cosh ax] = L[ ]= L[e ] + L[e ] = + = 2 ,
2 2 2 s−a s+a s − a2
eax − e−ax
1 1 1 1 a
L[sinh ax] = L[ ]= L[eax ] − L[e−ax ] = − = 2 .
2 2 2 s−a s+a s − a2
Theorem 6.17.
If L[f (x)] = F (s), then the following hold:
1. L[eax f (x)] = F (s − a);
1 s
2. L[f (ax)] = F ( );
a ′a
3. L[xf (x)] = −F (s);
4. L[fZ ′ (x)] = sF (s) − f (0);
x
1
5. L[ f (t) dt] = F (s).
0 s
Proof Z ∞ Z ∞
ax −sx ax
1. L[e f (x)] = e e f (x) dx = e−(s−a)x f (x) dx = F (s − a).
0 0
∞ ∞
1 1 s
Z Z
sξ
2. L[f (ax)] = e−sx f (ax) dx = e− a f (ξ) dξ = F ( ).
0 a 0 a a
∞ ∞
d
Z Z
−sx
3. L[xf (x))] = e xf (x)) dx = − e−sx f (x) dx = −F ′ (s).
0 ds 0
Z ∞ ∞ Z ∞
−sx ′ −sx
′
4. L[f (x))] = e f (x)) dx = e f (x) + s
e−sx f (x) dx = −f (0) + sF (s).
0 0 0
Z ∞
5. Let g(x) := f (t) dt and G(s) := L[g(x)]. Then g′ (x) = f (x) and g(0) = 0. We now have
0
F (s) = L[f (x)] = L[g′ (x)] = sG(s) − g(0) = sG(s) (using property 4). Therefore
Z x
1
L[ f (t) dt] = L[g(x)] = G(s) = F (s).
0 s
Math 334 6.2. PROPERTIES OF LAPLACE TRANSFORMS 87
Remark.
1. Formula 4 can be extended as follows:
Let g(x) = f ′ (x). Then G(s) = L[g(x)] = L[f ′ (x)] = sF (s) − f (0).
This leads to
L[f ′′ (x)] = L[g′ (x)] = sG(s) − g(0) = s(sF (s) − f (0)) − f ′ (0) = s2 F (s) − sf (0) − f ′ (0).
These properties of the Laplace transform allow us to build up a table of Laplace transforms without having
to actually integrate.
Example 6.18.
d d 1 1
1. L[x] = L[x · 1] = − L[1] = − = 2 . (using property 3)
ds ds s s
Z x
1 1 1 1
2. L[x] = L[ 1 dt] = L[1] = · = 2 . (using property 5)
0 s s s s
2 d d 1 2
3. L[x ] = L[x · x] = − L[x] = − 2
= 3 . (using property 3)
ds ds s s
Z x
2 2 1 2
4. L[x2 ] = L[ 2t dt] = L[x] = · 2 = 3 . (using property 5)
0 s s s s
1
5. L[eax ] = L[eax · 1] = L[1](s − a) =
. (using property 1)
s−a
ax d ax d 1 1
6. L[x e ] = − L[e ] = − = . (using property 3)
ds ds s − a (s − a)2
1
7. L[x eax ] = L[x](s − a) = . (using property 1)
(s − a)2
s−a
8. L[eax cos bx] = L[cos bx](s − a) = . (using property 1)
b2 + (s − a)2
One situation for which Laplace transforms are particularly useful is in solving differerential equations with
discontinuous coefficients. Let (
x2 0 6 x < 2
f (x) = . (6.1)
0 x>2
Math 334 6.2. PROPERTIES OF LAPLACE TRANSFORMS 88
Calculating the Laplace transform requires integration by parts twice leading to:
Z ∞ Z 2
F (s) = L[f (x)] = e−sx f (x) dx = x2 e−sx dx
0 0
2
2
x 2x 2 2 4 4 2
=− + 2 + 3 e−sx = 3 − + 2 + 3 e−2s .
s s s 0 s s s s
It turns out that the above calculation can be simplified by using the unit step function. Define
(
0 x<a
ua (x) := .
1 x>a
Now consider the functions f (x) and f (x)ua(x) in the Figure 6.2 below.
y y
y=f(x) y=f(x)ua(x)
a x a x
We can think of the unit step function ua (x) as a switch, so that f (x)ua (x) “turns on” f (x) at x = a.
Similarly, f (x)ub(x) “turns on” f (x) at x = b. Therefore f (x)[ua(x) − ub (x)] “turns on” f (x) at x = a and
“turns off” f (x) at x = b. See Figure 6.3.
(
0 x<a
f (x)ua(x) =
0 x<a
f (x) x > a
( =⇒ f (x)[u a (x) − u b (x)] = f (x) a6x<b.
0 x<b
0 x>b
f (x)ub(x) =
f (x) x > b
y=f(x)[ua(x)-ub(x)]
a b x
Theorem 6.19.
If L[f (x)] exists, then L[f (x)ua(x)] = e−ax L[f (x + a)].
Proof
Z ∞ Z ∞
−st
L[f (x)ua (x)] = e e−stf (t) dt
f (t)ua(t) dt =
0 a
Z ∞ Z ∞
= e−s(x+a) f (x + a) dx = e−as e−sx f (x + a) dx = e−as L[f (x + a)].
0 0
Let us return to the function defined in Eq. (6.1). Using unit step functions f (x) = x2 [u0 (x) − u2 (x)].
Calculating the Laplace transform we get
L[f (x)] = L[x2 u0 (x)] − L[x2 u2 (x)] = e−0s L[(x + 0)2 ] − e−2s L[(x + 2)2 ]
2 4 4 2
= L[x2 ] − e−2s L[x2 + 4x + 4] = 3 − e−2s + 2+ 3 .
s s s s
Definition 6.20. A funtion f is periodic with period p if f (x + np) = f (x) for all n ∈ Z. ◭
Theorem 6.21. p
1
Z
If (i) f ∈ F1 , and (ii) f is periodic with period p, then L[f (x)] = f (x)e−sx dx.
1 − e−ps 0
Proof
First, we have
Z (n+1)p Z p Z p
e−sx f (x) dx = e−s(t+np) f (t + np) dt = e−nps e−st f (t) dt.
np 0 0
2π
Example 6.22. The function cos ax is periodic with period p = . Using the result of the previous
a
Math 334 6.2. PROPERTIES OF LAPLACE TRANSFORMS 90
theorem we get
2π 2π
1 1 e−sx
Z a
−sx
a
L[cos ax] = e cos ax dx = 2 2
(a sin ax − s cos ax)
1−e
−2πs
a 0 1−e
−2πs
a s +a 0
( −2πs )
1 e a (−s) − (−s) s
= = 2 .
1−e
−2πs
a s2 + a2 s + a2
Solution
The function f is periodic with period 2, so we have
Z 2 Z 1 Z 2
1 −sx 1 −sx −sx
L[f (x)] = e f (x) dx = e dx − e dx
1 − e−2s 0 1 − e−2s 0 1
(1 − e−s )2 es/2 − e−s/2
−2s
1 e − 2e−s + 1 1 − e−s 1 1
= = = = = tanh( ).
1 − e−2s s s(1 − e−2s ) s(1 + e−s s(es/2 + e−s/2 ) s s